PENTINGNYA KELENGKAPAN FASILITAS SEKOLAH TERHADAPKENYAMANAN BELAJAR SISWA DI SDN 008 SAMARINDA ULU - Euis Kusumarini; Eka Selvi Handayani; Suprianata (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2022)
School facilities are synonymous with educational facilities and infrastructure. Educational facilities are all equipment, materials and parabots that can directly be used in the educational process in schools and educational infrastructure, namely all basic equipment or equipment that indirectly supports the implementation of the educational process in schools. The purpose of this study was to determine the importance of the completeness of school facilities and the convenience of student learning. Data collection methods in this study are documentation and interviews. To test the validity of the data in this study, researchers used source triangulation. The results of this study are that SD Negeri 008 Samarinda Ulu is an A-accredited high achieving school that has very adequate facilities. In addition, SD Negeri 008 Samarinda Ulu also provides opportunities for students to explore their own potential based on their hobbies and hobbies by using existing facilities at school as a method of supporting teaching and learning activities. Facilities are very important for schools because all school facilities can be used by all school staff from school principals, teachers and students to facilitate the learning process, besides that convenience is also very influential for learning and can increase student learning enthusiasm, in the Covid-19 pandemic situation how learning continues, namely using cellphone media as learning media because facilities and infrastructure play an important role in a school to support all activities and achieve a goal that is achieved, especially in learning, namely to make it easier for students to learn and create a calm and comfortable learning atmosphere.